Perovskite solar cell, preparation method thereof and photovoltaic module
By introducing 3-hydroxyphenylboric acid as the interface modification layer in perovskite solar cells, the problem of uneven coverage of the perovskite layer is solved, and the battery performance is improved, including photoelectric conversion efficiency and filling factor.
Patent Information
- Application Number
- CN202411439616.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-14
AI Technical Summary
In perovskite solar cells, the perovskite layer covers the hole transport layer unevenly, resulting in limited battery performance.
3-hydroxyphenylboric acid is introduced at the adjacent interface between the perovskite layer and the hole transport layer to form an interface modification layer, improve the wettability of the hole transport layer, and reduce non-radiative recombination through coordination.
The coverage and quality of the perovskite layer are improved, the carrier transmission efficiency is enhanced, and the photoelectric conversion efficiency, filling factor, open circuit voltage and short circuit current of solar cells are improved.
Smart Images

Figure CN119451513A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and in particular to a perovskite solar cell and a preparation method thereof, and a photovoltaic module. Background Art
[0002] Among the structures of perovskite solar cells, pin-structured perovskite solar cells stand out for their high photoelectric conversion rate and excellent stability. Self-assembled monolayer (SAM) materials are usually used in solar cells with this structure. SAM materials not only have unique dipole properties that can effectively promote the extraction of photocarriers, but also show excellent electron blocking and hole selection capabilities. At the same time, they form a strong binding force with substrates such as ITO glass, making the perovskite solar cells with this structure show great potential in performance. However, there is still a major challenge in practical applications: the perovskite layer formed by the perovskite precursor solution often cannot completely cover the hole transport layer due to the hydrophobic properties of the SAM material, resulting in limited performance of the solar cell.
[0003] To address this problem, existing solutions mainly include adding additives to the perovskite precursor solution or SAM material to improve wettability, and using ozone and other equipment to treat the surface of the hole transport layer to repair the defects of the perovskite layer. However, these methods all have certain limitations: although the addition of additives can improve wettability to a certain extent, the effect is not significant, and the additives in the SAM material will also affect the hole extraction ability, and the effect of the surface treatment method has not met expectations, making it difficult to fundamentally solve the problem.
[0004] Accordingly, the art needs a new technical solution to solve the above problems. Summary of the invention
[0005] In order to solve at least one of the above problems in the prior art, that is, to solve the problem that the uneven coverage of the hole transport layer by the perovskite layer affects the battery performance, the present application provides a method for preparing a perovskite solar cell, comprising the following steps:
[0006] preparing a hole transport layer on a substrate;
[0007] preparing an interface modification layer on the prepared hole transport layer;
[0008] Preparing a perovskite layer on the prepared interface modification layer;
[0009] Sequentially preparing an electron transport layer and an electrode on the obtained perovskite layer to obtain a perovskite solar cell;
[0010] Wherein, the material for preparing the interface modification layer is 3-hydroxyphenylboric acid.
[0011] In the preferred technical solution of the above preparation method, the step of preparing the interface repair layer comprises:
[0012] The 3-hydroxyphenylboronic acid solution is deposited on the hole transport layer, and then heated and annealed to obtain the interface modification layer.
[0013] In the preferred technical solution of the above preparation method, one or more of the following features are possessed:
[0014] The concentration of the 3-hydroxyphenylboronic acid solution is 0.6-1 mg / mL;
[0015] The annealing temperature is 100-150° C. and the annealing time is 10-15 minutes.
[0016] In the preferred technical solution of the above preparation method, the SAM material solution for preparing the hole transport layer is deposited on the substrate, and then heated and annealed to obtain the hole transport layer; and / or
[0017] The perovskite precursor solution for preparing the perovskite layer is deposited on the interface modification layer, and then heated and annealed to obtain the perovskite layer.
[0018] In the preferred technical solution of the above preparation method, one or more of the following features are possessed:
[0019] The SAM material includes one or more of MeO-2PACZ, 2PACZ, and Me-4PACZ;
[0020] The perovskite precursor includes one or more of FAPbI3, FAMAPbI, FACsPbI, and FAMACsPbI;
[0021] The concentration of the SAM material solution is 0.4-0.6 mg / mL;
[0022] The concentration of the perovskite precursor solution is 1-1.4 mmol / L;
[0023] In the process of preparing the hole transport layer and the perovskite layer, the annealing temperature is 100-150° C. and the time is 10-15 minutes.
[0024] In the preferred technical solution of the above preparation method, one or more of the following features are possessed:
[0025] The material for preparing the electron transport layer is C 60 and at least one of PCBM;
[0026] The substrate is FTO glass, ITO glass or a flexible ITO conductive substrate.
[0027] In the preferred technical solution of the above preparation method, before preparing the electrode, the method further comprises:
[0028] preparing a hole blocking layer on the electron transport layer;
[0029] The electrode is prepared on the hole blocking layer.
[0030] In a preferred technical solution of the above preparation method, the method for preparing the hole blocking layer includes: chemically depositing the material for preparing the hole blocking layer on the electron transport layer to form the hole blocking layer.
[0031] In the preferred technical solution of the above preparation method, the material used to prepare the hole blocking layer is BCP.
[0032] The present application also provides a perovskite solar cell, which includes a substrate and a hole transport layer, an interface modification layer, a perovskite layer, an electron transport layer and an electrode sequentially arranged on the substrate, wherein the material of the interface modification layer is 3-hydroxyphenylboric acid.
[0033] The present application also provides a photovoltaic module, which includes a perovskite solar cell prepared by the preparation method described in the above preferred technical solution, or a perovskite solar cell described in the above preferred technical solution.
[0034] It can be understood by those skilled in the art that the preparation method of the perovskite solar cell of the present application can improve the wettability of the hole transport layer by introducing 3-hydroxyphenylboric acid at the adjacent interface between the perovskite layer and the hole transport layer, thereby increasing the coverage of the perovskite layer and improving the quality of the perovskite layer. At the same time, 3-hydroxyphenylboric acid coordinates with the metal ions in the perovskite layer, which can reduce the non-radiative recombination between the interface of the hole transport layer and the perovskite layer and improve the carrier transmission efficiency.
[0035] Furthermore, by using a 3-hydroxyphenylboric acid solution with a concentration of 0.4-0.6 mg / mL to prepare an interface modification layer, the photoelectric conversion efficiency, fill factor, open circuit voltage and short circuit current of the perovskite solar cell can be improved.
[0036] Furthermore, by using one or more of FAPbI3, MeO-2PACZ, 2PACZ, and Me-4PACZ to prepare the hole transport layer, the wettability can be improved by 3-hydroxyphenylboric acid, thereby improving the battery performance of the perovskite solar cell. By using one or more of FAPbI3, FAMAPbI, FACsPbI, and FAMACsPbI to prepare the perovskite precursor, 3-hydroxyphenylboric acid can be coordinated with the lead ions in the perovskite precursor, thereby reducing the non-radiative recombination between the hole transport layer and the perovskite layer interface.
[0037] Furthermore, by preparing a hole blocking layer on the electron transport layer, holes can be blocked, the recombination of electrons and holes can be reduced, and the photoelectric conversion efficiency of the perovskite solar cell can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The preferred technical solution of the present application is described below with reference to the accompanying drawings. In the accompanying drawings:
[0039] Figure 1 A structural diagram of a perovskite solar cell with a nip structure in the prior art;
[0040] Figure 2 A structural diagram of a perovskite solar cell with a pin structure in the prior art;
[0041] Figure 3 A structural diagram of a perovskite solar cell of the present application;
[0042] Figure 4 Flow chart of the method for preparing a perovskite solar cell of the present application. DETAILED DESCRIPTION
[0043] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Combination Figure 3 and Figure 4 , the preparation method of the perovskite solar cell of the present application is described.
[0045] See also Figure 1 and Figure 2 In the prior art, perovskite solar cells include NIP-structured perovskite solar cells and PIN-structured perovskite solar cells. NIP-structured perovskite solar cells, also known as forward-structured perovskite solar cells, include a substrate, an electron transport layer, a perovskite layer, a hole transport layer, and an electrode. PIN-structured perovskite solar cells, also known as reverse-structured perovskite solar cells, include a substrate, a hole transport layer, a perovskite layer, an electron transport layer, and an electrode. Compared with NIP-structured perovskite solar cells, PIN-structured perovskite solar cells have high photoelectric conversion efficiency and good stability. However, the perovskite layer has uneven coverage on the hole transport layer, which affects the performance of the solar cell, such as blocked charge transfer, decreased short-circuit current and opening voltage, etc.
[0046] like Figure 3 and Figure 4 In order to solve the problem of uneven coverage of the hole transport layer by the perovskite layer, the present application provides a perovskite solar cell, including a substrate and a hole transport layer, an interface modification layer, a perovskite layer, an electron transport layer and an electrode sequentially arranged on the substrate, wherein the material of the interface modification layer is 3-hydroxyphenylboric acid.
[0047] The present application introduces 3-hydroxyphenylboric acid at the adjacent interface between the perovskite layer and the hole transport layer, thereby improving the wettability of the hole transport layer, thereby increasing the coverage of the perovskite layer and improving the quality of the perovskite layer. At the same time, 3-hydroxyphenylboric acid coordinates with metal ions in the perovskite layer, thereby reducing non-radiative recombination between the interface of the hole transport layer and the perovskite layer and improving the carrier transmission efficiency.
[0048] The method for preparing the above-mentioned perovskite solar cell comprises the following steps:
[0049] preparing a hole transport layer on a substrate;
[0050] preparing an interface modification layer on the prepared hole transport layer;
[0051] preparing a perovskite layer on the prepared interface modification layer;
[0052] An electron transport layer and an electrode are sequentially prepared on the obtained perovskite layer to obtain a perovskite solar cell;
[0053] Wherein, the material for preparing the interface modification layer is 3-hydroxyphenylboric acid.
[0054] Specifically, in step 101), a hole transport layer is prepared on a substrate.
[0055] Wherein, the substrate is a transparent conductive substrate, which can be FTO glass, ITO glass or flexible ITO conductive substrate, and the specific substrate technicians can adjust according to the needs of the setting. In addition, before preparing the hole transport layer on the substrate, step 100) is also included to clean the substrate. For example, the substrate can be cleaned in an ultrasonic device using detergent water, deionized water, and ethanol in sequence, and nitrogen can be used to blow dry for standby after each cleaning, and each cleaning time can be 10-30min. And / or, the substrate after cleaning can be treated with ultraviolet ozone UV-zone, and the processing time can be 10-30min. By treating the substrate with ozone, the cleanliness, wettability, conductivity and oxidation resistance of the substrate can be improved, making the perovskite solar cell more stable.
[0056] The method for preparing a hole transport layer on a substrate comprises: depositing a SAM material solution for preparing a hole transport layer on the hole transport layer, and then heating and annealing to obtain a hole transport layer. The concentration of the SAM material solution is 0.4-0.6 mg / mL, and the solvent can be ethanol, isopropanol, or a mixed solvent of ethanol and isopropanol with a volume ratio of 1-2:1. The SAM material solution can be deposited on the substrate by spin coating, spraying, etc. Preferably, the SAM material solution is deposited on the substrate by spin coating. The annealing time is 10-30 min, and the temperature is 100-150°C. The SAM material includes one or more of MeO-2PACZ (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethylphosphonic acid), 2PACZ (2-(9H-carbazole-9-yl)ethylphosphonic acid), and Me-4PACZ (4-(3,6-dimethyl-9H-carbazole-9-yl)butylphosphonic acid). All three materials include carbazole and phosphonic acid. Carbazole has relatively low ionization energy and low electron affinity, so that the hole transport layer has the characteristics of electron blocking and hole selection; the phosphonic acid group is strongly bound to the substrate surface through a combination of double bonds and trident bonds.
[0057] Step 102), preparing an interface modification layer on the hole transport layer.
[0058] The method for preparing an interface modification layer on a hole transport layer comprises: depositing a 3-hydroxyphenylboric acid solution on the hole transport layer, and then heating and annealing to obtain an interface modification layer. The concentration of the 3-hydroxyphenylboric acid solution is 0.6-1 mg / mL, and the solvent can be ethanol, isopropanol, or a mixed solvent of ethanol and isopropanol. The 3-hydroxyphenylboric acid solution can be deposited on the hole transport layer by spin coating, spraying, etc. Preferably, the 3-hydroxyphenylboric acid solution is deposited on the hole transport layer by spin coating. The annealing temperature is 100-150°C and the time is 10-15min. By using 3-hydroxyphenylboric acid as an interface modification layer, the hydroxyl group in the 3-hydroxyphenylboric acid can improve the problem of uneven coverage of the perovskite layer due to the hydrophobicity of the SAM material. The use of 3-hydroxyphenylboric acid solution with the above concentration to prepare the interface modification layer can improve the photoelectric conversion efficiency (PCE), fill factor (FF), open circuit voltage (VOC) and short circuit current (JSC) of the perovskite solar cell, while the concentration of the 3-hydroxyphenylboric acid solution higher or lower than the above range will affect the photoelectric conversion efficiency (PCE), fill factor (FF), open circuit voltage (VOC) and short circuit current (JSC) of the perovskite solar cell.
[0059] Step 103), preparing a perovskite layer on the interface modification layer.
[0060] The method for preparing a perovskite layer on an interface modification layer comprises: depositing a perovskite precursor solution on the interface modification layer, and then heating and annealing to obtain a perovskite layer. Wherein, the concentration of the perovskite precursor solution is 1-1.4mmol / L, and the solvent is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide, or a mixed solvent of γ-butyrolactone and N-methylpyrrolidone. When the solvent is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide, the volume ratio of N,N-dimethylformamide and dimethyl sulfoxide is 3-5:1. When the solvent is a mixed solvent of γ-butyrolactone and N-methylpyrrolidone, the volume ratio of γ-butyrolactone and N-methylpyrrolidone is 3-5:1. The perovskite precursor solution can be deposited on the interface modification layer by spin coating, spray coating, etc. Preferably, the perovskite precursor solution is deposited on the interface modification layer by spin coating. The annealing temperature is 100-150°C and the time is 10-15min. The perovskite precursor includes one or more of FAPbI3 (formamidine-lead-iodine), FAMAPbI (formamidine-methylammonium-lead-iodine), FACsPbI (formamidine-cesium-lead-iodine), and FAMACsPbI (formamidine-methylammonium-cesium-lead-iodine). By using the above perovskite precursor, 3-hydroxyphenylboric acid can be coordinated with the lead ions in the perovskite precursor, which can reduce the non-radiative recombination between the hole transport layer and the perovskite layer interface, improve the carrier transmission efficiency, and ultimately achieve the purpose of improving the photoelectric conversion efficiency, fill factor, open circuit voltage and short circuit current of the perovskite solar cell.
[0061] Step 104), sequentially preparing an electron transport layer and an electrode on the perovskite layer to obtain a perovskite solar cell.
[0062] The method for preparing an electron transport layer on a perovskite layer comprises: chemically depositing a material for preparing the electron transport layer on the perovskite layer to form the electron transport layer. The material for preparing the electron transport layer is C 60 At least one of and PCBM, the above materials can be deposited on the perovskite layer by evaporation.
[0063] Before preparing the electrode on the electron transport layer, a hole blocking layer is also prepared on the electron transport layer. The method for preparing the hole blocking layer on the electron transport layer includes: chemically depositing the material for preparing the hole blocking layer on the electron transport layer to form the hole blocking layer. Among them, the material for preparing the hole blocking layer is BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline), and the above material can be deposited on the electron transport layer by evaporation.
[0064] The method for preparing an electrode on the hole blocking layer includes: chemically depositing the material for preparing the electrode on the electron transport layer to form the electrode, wherein the electrode is a metal electrode, such as a silver electrode, and the above material can be deposited on the hole blocking layer by evaporation.
[0065] In addition, the present application also provides a photovoltaic module, which includes the perovskite solar cell described in any of the above embodiments.
[0066] Among them, the perovskite solar cell has been described above and will not be repeated here.
[0067] The perovskite solar cell prepared in the present application is described in conjunction with the following examples.
[0068] Example 1
[0069] Step 100: placing the FTO glass in an ultrasonic cleaning device, and cleaning the FTO glass with detergent water, deionized water, and ethanol respectively, with each detergent cleaning time being 20 minutes, and drying with nitrogen after each detergent cleaning; treating the ultrasonically cleaned FTO glass with a UV-zone for 20 minutes;
[0070] Step 101: Prepare a Me-4PACZ solution with a concentration of 0.6 mg / ml, using ethanol as the solvent, and stir for standby use; take 50 μL of the Me-4PACZ solution and spin-coat it on the FTO glass at a spin-coating speed of 3000 rpm for 30 seconds, and then anneal at 100° C. for 10 minutes to obtain a hole transport layer;
[0071] Step 102: preparing a 0.8 mg / ml 3-hydroxyphenylboric acid solution with ethanol as the solvent, stirring for standby use; taking 50 μL of the 3-hydroxyphenylboric acid solution and spin coating it on the hole transport layer at a spin coating speed of 3000 rpm for 30 seconds, and then annealing at 100° C. for 10 minutes to obtain an interface modification layer;
[0072] Step 103: prepare a FAPbI3 solution with a concentration of 1.2 mmol / L, wherein the solvent is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1, and stir for standby use; take 80 μL of the FAPbI3 solution and spin-coat it on the interface modification layer at a spin-coating speed of 5000 rpm for 30 seconds, and add 300 μL of anisole 5 seconds before the spin-coating process is about to end to obtain a perovskite wet film; then anneal at 150° C. for 10 minutes to obtain a perovskite layer;
[0073] Step 104: On the prepared perovskite layer Evaporation 30nm C 60 , to obtain an electron transport layer; and then on the prepared electron transport layer 6nm BCP was evaporated to obtain a hole blocking layer; finally, a 110nm silver electrode was formed on the hole blocking layer.
[0074] Example 2
[0075] Step 100: placing the FTO glass in an ultrasonic cleaning device, and cleaning the FTO glass with detergent water, deionized water, and ethanol respectively, with each detergent cleaning time being 20 minutes, and drying with nitrogen after each detergent cleaning; treating the ultrasonically cleaned FTO glass with a UV-zone for 20 minutes;
[0076] Step 101: Prepare a Me-4PACZ solution with a concentration of 0.6 mg / ml, using ethanol as the solvent, and stir for standby use; take 50 μL of the Me-4PACZ solution and spin-coat it on the FTO glass at a spin-coating speed of 3000 rpm for 30 seconds, and then anneal at 100° C. for 10 minutes to obtain a hole transport layer;
[0077] Step 102: preparing a 3-hydroxyphenylboronic acid solution with a concentration of 1 mg / ml, using ethanol as the solvent, stirring for standby use; taking 50 μL of the 3-hydroxyphenylboronic acid solution and spin coating it on the hole transport layer at a spin coating speed of 3000 rpm for 30 seconds, and then annealing at 100° C. for 10 minutes to obtain an interface modification layer;
[0078] Step 103: prepare a FAPbI3 solution with a concentration of 1.2 mmol / L, wherein the solvent is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1, and stir for standby use; take 80 μL of the FAPbI3 solution and spin-coat it on the interface modification layer at a spin-coating speed of 5000 rpm for 30 seconds, and add 300 μL of anisole 5 seconds before the spin-coating process is about to end to obtain a perovskite wet film; then anneal at 150° C. for 10 minutes to obtain a perovskite layer;
[0079] Step 104: On the prepared perovskite layer Evaporation 30nm C 60 , to obtain an electron transport layer; and then on the prepared electron transport layer 6nm BCP was evaporated to obtain a hole blocking layer; finally, a 110nm silver electrode was formed on the hole blocking layer.
[0080] Example 3
[0081] Step 100: placing the FTO glass in an ultrasonic cleaning device, and cleaning the FTO glass with detergent water, deionized water, and ethanol respectively, with each detergent cleaning time being 20 minutes, and drying with nitrogen after each detergent cleaning; treating the ultrasonically cleaned FTO glass with a UV-zone for 20 minutes;
[0082] Step 101: Prepare a Me-4PACZ solution with a concentration of 0.6 mg / ml, using ethanol as the solvent, and stir for standby use; take 50 μL of the Me-4PACZ solution and spin-coat it on the FTO glass at a spin-coating speed of 3000 rpm for 30 seconds, and then anneal at 100° C. for 10 minutes to obtain a hole transport layer;
[0083] Step 102: preparing a 0.6 mg / ml 3-hydroxyphenylboric acid solution with ethanol as the solvent, stirring for standby use; taking 50 μL of the 3-hydroxyphenylboric acid solution and spin coating it on the hole transport layer at a spin coating speed of 3000 rpm for 30 seconds, and then annealing at 100° C. for 10 minutes to obtain an interface modification layer;
[0084] Step 103: prepare a FAPbI3 solution with a concentration of 1.2 mmol / L, wherein the solvent is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1, and stir for standby use; take 80 μL of the FAPbI3 solution and spin-coat it on the interface modification layer at a spin-coating speed of 5000 rpm for 30 seconds, and add 300 μL of anisole 5 seconds before the spin-coating process is about to end to obtain a perovskite wet film; then anneal at 150° C. for 10 minutes to obtain a perovskite layer;
[0085] Step 104: On the prepared perovskite layer Evaporation 30nm C 60 , to obtain an electron transport layer; and then on the prepared electron transport layer 6nm BCP was evaporated to obtain a hole blocking layer; finally, a 110nm silver electrode was formed on the hole blocking layer.
[0086] Comparative Example 1
[0087] Step 100: placing the FTO glass in an ultrasonic cleaning device, and cleaning the FTO glass with detergent water, deionized water, and ethanol respectively, with each detergent cleaning time being 20 minutes, and drying with nitrogen after each detergent cleaning; treating the ultrasonically cleaned FTO glass with a UV-zone for 20 minutes;
[0088] Step 101: Prepare a Me-4PACZ solution with a concentration of 0.6 mg / ml, using ethanol as the solvent, and stir for standby use; take 50 μL of the Me-4PACZ solution and spin-coat it on the FTO glass at a spin-coating speed of 3000 rpm for 30 seconds, and then anneal at 100° C. for 10 minutes to obtain a hole transport layer;
[0089] Step 102: prepare a FAPbI3 solution with a concentration of 1.2 mmol / L, wherein the solvent is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1, and stir for standby use; take 80 μL of the FAPbI3 solution and spin-coat it on the interface modification layer at a spin-coating speed of 5000 rpm for 30 seconds, and add 300 μL of anisole 5 seconds before the spin-coating process is about to end to obtain a perovskite wet film; then anneal at 150° C. for 10 minutes to obtain a perovskite layer;
[0090] Step 103: On the prepared perovskite layer Evaporation 30nm C 60 , to obtain an electron transport layer; and then on the prepared electron transport layer 6nm BCP was evaporated to obtain a hole blocking layer; finally, a 110nm silver electrode was formed on the hole blocking layer.
[0091] Comparative Example 2
[0092] Step 100: placing the FTO glass in an ultrasonic cleaning device, and cleaning the FTO glass with detergent water, deionized water, and ethanol respectively, with each detergent cleaning time being 20 minutes, and drying with nitrogen after each detergent cleaning; treating the ultrasonically cleaned FTO glass with a UV-zone for 20 minutes;
[0093] Step 101: Prepare a Me-4PACZ solution with a concentration of 0.6 mg / ml, using ethanol as the solvent, and stir for standby use; take 50 μL of the Me-4PACZ solution and spin-coat it on the FTO glass at a spin-coating speed of 3000 rpm for 30 seconds, and then anneal at 100° C. for 10 minutes to obtain a hole transport layer;
[0094] Step 102: preparing a 0.4 mg / ml 3-hydroxyphenylboric acid solution with ethanol as the solvent, stirring for standby use; taking 50 μL of the 3-hydroxyphenylboric acid solution and spin coating it on the hole transport layer at a spin coating speed of 3000 rpm for 30 seconds, and then annealing at 100° C. for 10 minutes to obtain an interface modification layer;
[0095] Step 103: prepare a FAPbI3 solution with a concentration of 1.2 mmol / L, wherein the solvent is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1, and stir for standby use; take 80 μL of the FAPbI3 solution and spin-coat it on the interface modification layer at a spin-coating speed of 5000 rpm for 30 seconds, and add 300 μL of anisole 5 seconds before the spin-coating process is about to end to obtain a perovskite wet film; then anneal at 150° C. for 10 minutes to obtain a perovskite layer;
[0096] Step 104: On the prepared perovskite layer Evaporation 30nm C 60 , to obtain an electron transport layer; and then on the prepared electron transport layer 6nm BCP was evaporated to obtain a hole blocking layer; finally, a 110nm silver electrode was formed on the hole blocking layer.
[0097] Comparative Example 3
[0098] Step 100: placing the FTO glass in an ultrasonic cleaning device, and cleaning the FTO glass with detergent water, deionized water, and ethanol respectively, with each detergent cleaning time being 20 minutes, and drying with nitrogen after each detergent cleaning; treating the ultrasonically cleaned FTO glass with a UV-zone for 20 minutes;
[0099] Step 101: Prepare a Me-4PACZ solution with a concentration of 0.6 mg / ml, using ethanol as the solvent, and stir for standby use; take 50 μL of the Me-4PACZ solution and spin-coat it on the FTO glass at a spin-coating speed of 3000 rpm for 30 seconds, and then anneal at 100° C. for 10 minutes to obtain a hole transport layer;
[0100] Step 102: preparing a 3-hydroxyphenylboronic acid solution with a concentration of 1.2 mg / ml, using ethanol as the solvent, stirring for standby use; taking 50 μL of the 3-hydroxyphenylboronic acid solution and spin coating it on the hole transport layer at a spin coating speed of 3000 rpm for 30 seconds, and then annealing at 100° C. for 10 minutes to obtain an interface modification layer;
[0101] Step 103: prepare a FAPbI3 solution with a concentration of 1.2 mmol / L, wherein the solvent is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1, and stir for standby use; take 80 μL of the FAPbI3 solution and spin-coat it on the interface modification layer at a spin-coating speed of 5000 rpm for 30 seconds, and add 300 μL of anisole 5 seconds before the spin-coating process is about to end to obtain a perovskite wet film; then anneal at 150° C. for 10 minutes to obtain a perovskite layer;
[0102] Step 104: On the prepared perovskite layer Evaporation 30nm C 60 , to obtain an electron transport layer; and then on the prepared electron transport layer 6nm BCP was evaporated to obtain a hole blocking layer; finally, a 110nm silver electrode was formed on the hole blocking layer.
[0103] Comparative Example 4
[0104] Step 100: placing the FTO glass in an ultrasonic cleaning device, and cleaning the FTO glass with detergent water, deionized water, and ethanol respectively, with each detergent cleaning time being 20 minutes, and drying with nitrogen after each detergent cleaning; treating the ultrasonically cleaned FTO glass with a UV-zone for 20 minutes;
[0105] Step 101: Prepare a Me-4PACZ solution with a concentration of 0.6 mg / ml, using ethanol as the solvent, and stir for standby use; take 50 μL of the Me-4PACZ solution and spin-coat it on the FTO glass at a spin-coating speed of 3000 rpm for 30 seconds, and then anneal at 100° C. for 10 minutes to obtain a hole transport layer;
[0106] Step 102: preparing a 2-hydroxyphenylboric acid solution with a concentration of 0.8 mg / ml, using ethanol as the solvent, stirring for standby use; taking 50 μL of the 3-hydroxyphenylboric acid solution and spin coating it on the hole transport layer, the spin coating speed is 3000 rpm, the time is 30 seconds, and then annealing at 100° C. for 10 minutes to obtain an interface modification layer;
[0107] Step 103: prepare a FAPbI3 solution with a concentration of 1.2 mmol / L, wherein the solvent is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1, and stir for standby use; take 80 μL of the FAPbI3 solution and spin-coat it on the interface modification layer at a spin-coating speed of 5000 rpm for 30 seconds, and add 300 μL of anisole 5 seconds before the spin-coating process is about to end to obtain a perovskite wet film; then anneal at 150° C. for 10 minutes to obtain a perovskite layer;
[0108] Step 104: On the prepared perovskite layer Evaporation 30nm C 60 , to obtain an electron transport layer; and then on the prepared electron transport layer 6nm BCP was evaporated to obtain a hole blocking layer; finally, a 110nm silver electrode was formed on the hole blocking layer.
[0109] Comparative Example 5
[0110] Step 100: placing the FTO glass in an ultrasonic cleaning device, and cleaning the FTO glass with detergent water, deionized water, and ethanol respectively, with each detergent cleaning time being 20 minutes, and drying with nitrogen after each detergent cleaning; treating the ultrasonically cleaned FTO glass with a UV-zone for 20 minutes;
[0111] Step 101: Prepare a Me-4PACZ solution with a concentration of 0.6 mg / ml, using ethanol as the solvent, and stir for standby use; take 50 μL of the Me-4PACZ solution and spin-coat it on the FTO glass at a spin-coating speed of 3000 rpm for 30 seconds, and then anneal at 100° C. for 10 minutes to obtain a hole transport layer;
[0112] Step 102: prepare a 4-hydroxyphenylboric acid solution with a concentration of 0.8 mg / ml, the solvent is ethanol, and stir for standby use; take 50 μL of the 3-hydroxyphenylboric acid solution and spin-coat it on the hole transport layer at a spin-coating speed of 3000 rpm for 30 seconds, and then anneal at 100° C. for 10 minutes to obtain an interface modification layer;
[0113] Step 103: prepare a FAPbI3 solution with a concentration of 1.2 mmol / L, wherein the solvent is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1, and stir for standby use; take 80 μL of the FAPbI3 solution and spin-coat it on the interface modification layer at a spin-coating speed of 5000 rpm for 30 seconds, and add 300 μL of anisole 5 seconds before the spin-coating process is about to end to obtain a perovskite wet film; then anneal at 150° C. for 10 minutes to obtain a perovskite layer;
[0114] Step 104: On the prepared perovskite layer Evaporation 30nm C 60 , to obtain an electron transport layer; and then on the prepared electron transport layer 6nm BCP was evaporated to obtain a hole blocking layer; finally, a 110nm silver electrode was formed on the hole blocking layer.
[0115] The photoelectric conversion efficiency (PCE), fill factor (FF), open circuit voltage (VOC) and short circuit current (JSC) of the perovskite solar cells prepared in Examples 1-3 and Comparative Examples 1-5 were measured and the results are shown in Table 1.
[0116] Table 1 Performance parameters of perovskite solar cells
[0117] It can be seen from Table 1 that the perovskite solar cells prepared in Examples 1-3 show superior performance in photoelectric conversion efficiency, fill factor, open circuit voltage and short circuit current compared with Comparative Examples 1-5, and the battery performance is good.
[0118] Those skilled in the art will appreciate that, although some embodiments described herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the claims of the present application, any one of the claimed embodiments may be used in any combination.
[0119] It should be noted that although the detailed steps of the method of the present application are described in detail above, without departing from the basic principles of the present application, technical personnel in this field can combine, split and change the order of the above steps. The modified technical solution does not change the basic concept of the present application and therefore falls within the scope of protection of the present application.
[0120] So far, the technical solutions of the present application have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present application is obviously not limited to these specific embodiments. Without departing from the principles of the present application, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present application.
Claims
1. A method for preparing a perovskite solar cell, characterized in that: The following steps are involved: preparing a hole transport layer on a substrate; preparing an interface modification layer on the prepared hole transport layer; Preparing a perovskite layer on the prepared interface modification layer; Sequentially preparing an electron transport layer and an electrode on the obtained perovskite layer to obtain a perovskite solar cell; Wherein, the material for preparing the interface modification layer is 3-hydroxyphenylboric acid.
2. The preparation method according to claim 1, characterized in that: The steps of preparing the interface repair layer include: The 3-hydroxyphenylboronic acid solution is deposited on the hole transport layer, and then heated and annealed to obtain the interface modification layer.
3. The preparation method according to claim 2, characterized in that: Possess one or more of the following characteristics: The concentration of the 3-hydroxyphenylboronic acid solution is 0.6-1 mg / mL; The annealing temperature is 100-150° C. and the annealing time is 10-15 minutes.
4. The preparation method according to claim 1, characterized in that: The SAM material solution for preparing the hole transport layer is deposited on the substrate, and then heated and annealed to obtain the hole transport layer; and / or The perovskite precursor solution for preparing the perovskite layer is deposited on the interface modification layer, and then heated and annealed to obtain the perovskite layer.
5. The preparation method according to claim 4, characterized in that: Possess one or more of the following characteristics: The SAM material includes one or more of MeO-2PACZ, 2PACZ, and Me-4PACZ; The perovskite precursor includes one or more of FAPbI3, FAMAPbI, FACsPbI, and FAMACsPbI; The concentration of the SAM material solution is 0.4-0.6 mg / mL; The concentration of the perovskite precursor solution is 1-1.4 mmol / L; In the process of preparing the hole transport layer and the perovskite layer, the annealing temperature is 100-150° C. and the time is 10-15 minutes.
6. The preparation method according to claim 1, characterized in that: Possess one or more of the following characteristics: The material for preparing the electron transport layer is C 60 and at least one of PCBM; The substrate is FTO glass, ITO glass or a flexible ITO conductive substrate.
7. The preparation method according to claim 1, characterized in that: Before preparing the electrode, the method further comprises: preparing a hole blocking layer on the electron transport layer; The electrode is prepared on the hole blocking layer.
8. The preparation method according to claim 7, characterized in that: The method for preparing the hole blocking layer includes: chemically depositing the material for preparing the hole blocking layer on the electron transport layer to form the hole blocking layer; The material used to prepare the hole blocking layer is BCP.
9. A perovskite solar cell, characterized in that: The perovskite solar cell comprises a substrate and a hole transport layer, an interface modification layer, a perovskite layer, an electron transport layer and an electrode arranged in sequence on the substrate, and the material of the interface modification layer is 3-hydroxyphenylboric acid.
10. A photovoltaic module, characterized in that: The photovoltaic module comprises a perovskite solar cell prepared by the preparation method according to any one of claims 1 to 8, or a perovskite solar cell according to claim 9.
Citation Information
Cited By
High-efficiency perovskite photovoltaic device based on aromatic weak boric acid modification and preparation method thereof
CN119767998A
High-efficiency perovskite photovoltaic devices modified with aromatic weak boronic acid and preparation method thereof
CN119767998B
Flexible perovskite cell, preparation method thereof and photovoltaic module
CN121843338A
Flexible perovskite cell, preparation method thereof and photovoltaic module
CN121843338B